The Effect of Inorganic Fertilisers on the Growth of Deodar Seedlings - Rajkhowa, S. (Indian Forester, 1966)
An experiment carried out in Shillong (1,370 m) showed that though there was some indication of increase in height of Deodar seedlings on adding Superphosphate to the soil, there was a definite decrease in height growth on adding, Ammonium sulphate. In view of these results, the role of soil nitrogen in early growth and natural regeneration of Deodar stands needs further study.